Sensing the Squeeze of Sandwich Generation Women in Jakarta, Indonesia: Sensing the Squeeze of Sandwich Generation Women in Jakarta, Indonesia - Dian Kristiani Irawaty; Maria Gayatri (Journal of Family Sciences, 2023)
The majority of Indonesian women, known as "sandwich generations," have taken care of their young children and aging parents. Individual role-balancing challenges among these "sandwich" women have not yet, been fully investigated. This study aims to highlight Indonesian women's obstacles for being a sandwich generation. A qualitative descriptive case study through semi-structured interviews was carried out. A purposive sampling by key informants was conducted in June 2022 until saturation of the information was reached. This study involved six informants who live in Jakarta. Qualitative content analysis was carried out to generate codes and assign categories. From female respondent perspectives, males frequently provide financial support, whereas women are more likely to do so emotionally and assist with daily tasks like housework, grocery shopping, and personal cleanliness. Because of this, there was a significant conclusion that most sandwich-generation women received limited help during children and elderly care, evidencing the existence of other external factors favorable to physical, emotional, and mental stress and financial challenges.